Hormonal Contraceptives Use and Their Adverse Effects: A Cross-sectional Study among the Women Visiting Tertiary Care Center - Shakya Shrestha, S.; Shrestha, R.; Shrestha, S.; Koju, P.; Shrestha, A. (Kathmandu University Medical Journal, 2020)
Background Hormonal contraceptives are one of the most commonly used means of contraception. Lack of contraception may lead to large family size, increased preexisting illness on pregnancy, social and economic instability, risk of unsafe abortion and so on. This may also lead to unintended pregnancies which may alter the outcomes of pregnancies as well. However, improper uses are associated with several serious adverse effects. Therefore, to achieve the optimum benefit with the least adverse effects, safe and effective use of these agents with monitoring of their pattern of use and patient compliance is very essential. Objective To investigate the usage of hormonal contraceptives and the adverse effects associated with them. Method A cross-sectional study was conducted in a family planning center of a tertiary care hospital. All women of reproductive age using hormonal contraceptives for at least 1 month were included in this study. Informed consent was taken from the patients and interviewed using a structured questionnaire. Statistical analysis was performed by using SPSS 20. Result Among the 105 participants under this study, the mean (±SD) age was 29.08 (± 6.12) years. A majority (42, 40.0%) of them were using injectables. The average duration of use of hormonal contraceptives was 25.1 months ± 31.8 while a majority (60, 57.1%) were using contraceptives from < 3 months. Less chance of missed dose was the major reason (26.8%) for choosing injectable. Adverse effects were reported by 75.2% of the patients. The most common adverse effect was menstrual abnormalities (21.7%). Conclusion Among various hormonal contraceptives, injectables were more commonly used. The majority of the participants responded to use injectables because of the least chance of missing the dose. The most common adverse effect reported was menstrual abnormalities.